Urban expansion simulation towards low-carbon development: A case study of Wuhan, China. (December 2020) - Zhang, Yan; Liu, Yanfang; Wang, Yiheng; Liu, Dianfeng; Xia, Chang; Wang, Zhengyu; Wang, Haofeng; Liu, Yaolin
Highlights: Urban simulation aims for carbon emission reduction and sequestration conservation. The integrated Markov-BRL-CA is feasible to simulate constrained urban expansion. Four simulation scenarios based on different low-carbon strategies are designed. Low-carbon strategies benefit compact and sustainable urban development. Abstract: Rapid urbanization causes great changes of carbon metabolism. Current research mainly focuses on carbon consequences of urban expansion projections, but rarely explores how carbon management strategies affect future urban growth trajectories. Here, we propose a hierarchy of low-carbon management strategies and incorporate it into an integrated cellular automata model to obtain sustainable urban development plans. In the hierarchy, a top-down strategy regarding carbon emission reduction is used to adjust future urban land demand, while a bottom-up strategy regarding carbon sequestration conservation of land patches is used to constrain land use conversions. We design four expansion scenarios based on different combinations of the two low-carbon strategies for Wuhan in 2025, including business as usual (BAU), the scenario with top-town strategy (T-UES), the scenario with bottom-up strategy (B-UES), and the scenario with both two strategies (TB-UES). Our results demonstrate that the proposed method can generate promising urban expansion plans with less ecological loss, and promote compact and infilling urban development.